Artificial intelligence in medicine: legal, ethical and social aspects - Anishchenko, Mykhailo A.; Gidenko, Ievgen; Kaliman, Maksym; Polyvaniuk, Vasyl; Demianchuk, Yurii V. (Acta Bioethica, 2023)
In this article, the authors reflected the legal, ethical and social aspects of the introduction of artificial intelligence in the field of medicine. The authors used the dialectical method to understand the problematic aspects of qualitative changes in the healthcare system of Ukraine in connection with the quantitative increase in the use of artificial intelligence technology. The system method contributed to determining the nature of the impact of the introduction of artificial intelligence on the transformation of the structural elements of legislation in the healthcare sector. Analytical and formal-logical methods were useful in the process of identifying legal and ethical and social problems from the introduction of artificial intelligence and providing proposals for their solution. Emphasis was placed on the current state of the legal regulation of artificial intelligence in Ukraine and the problems of a legal, ethical and social nature that need to be addressed in the process of its implementation. The authors came to the conclusion that Ukraine is now at the initial stage of introducing artificial intelligence into public life. The problem of the lack of legislative work to streamline public relations associated with the use of artificial intelligence has been identified. Proposals are provided that can help mitigate the risks from the introduction of artificial intelligence.